An Analysis of Different Push and Pull Factors Responsible for Rural to Urban Migration in Hills of Uttarakhand - Neha Arya and R. Vasantha (Indian Journal of Extension Education, 2018)
Migration from the mountains of Uttarakhand to the other places is an age old practice and has its own importance in life of the mountain people. The present paper is an attempt to explore the possible push determinants (issues at the village/family/individual level) and pull determinants (attracting features of destination place) behind the increasing phenomenon of migration. The study conducted in the Uttarakhand state revealed that majority of the respondents migrated to destination opined that lack of employment opportunities in the villages (100%) and inability to meet basic needs with existing income (97.50%) compelled them for out migration. Majority of the migrants also perceived that the attractive features of destination areas such as high demand for labours (93.33%) and better employment opportunities (89.16%) were pull determinants that made them to migrate.